Witchcraft narratives in Germany : Rothenburg 1561-1652 - Rowlands, Alison (Manchester, UK ; New York : Manchester University Press ; New York : Distributed exclusively in the USA by Palgrave, 2003)
This text looks at why witch-trials failed to escalate into 'witch-crazes' in certain parts of early modern Europe. Using the legal records of Rothenburg ob der Tauber, the book explores the social and psychological conflicts behind the making of accusations and confessions of witchcraft.
Map: place of origin of the sixty-five people involved in witchtrials in Rothenburg ob der Tauber, 1549-1709 -- Introduction -- 'An honourable man should not talk about that which he cannot prove': slander and speech about witchcraft -- The devil's power to delude: elite beliefs about witchcraft and magic -- 'One cannot ... hope to obtain the slightest certainty from him': the first child-witch in Rothenburg, 1587 -- 'When will the burning start here?': the Catholic challenge during the Thirty Years' War -- Seduction, poison and magical theft: gender and contemporary fantasies of witchcraft -- 'God will punish both poor and rich': the idioms and risks of defiance in the trial of Margaretha Horn, 1652 -- Conclusion -- Appendix: trials for witchcraft in Rothenburg ob der Tauber, 1549-1709.
Includes bibliographical references (pages 229-238 and index.
Print version record.
English.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Witchcraft -- Germany -- Rothenburg ob der Tauber -- History -- 16th century; Witchcraft -- Germany -- Rothenburg ob der Tauber -- History -- 17th century; Sorcellerie -- Allemagne -- Rothenburg ob der Tauber -- Histoire -- 16e siècle.; Sorcellerie -- Allemagne -- Rothenburg ob der Tauber -- Histoire -- 17e siècle.; Humanities; History; Regional and national history; European history; BODY, MIND & SPIRIT -- Magick Studies; BODY, MIND & SPIRIT -- Witchcraft & Wicca; HISTORY -- Europe -- General; Witchcraft; Germany -- Rothenburg ob der Tauber; Hexenverfolgung; Rothenburg ob der Tauber; Heksenprocessen; Hekserij; 1500-1699; Geschichte 1561-1652.; Multi-User.; Electronic books; History